Kesesuaian Peningkatan Berat Badan Selama Kehamilan Berhubungan dengan Luaran Kehamilan - Sutik Indriyani; Fransisca Retno Asih; Machria Rachman (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
Globally, 53% of pregnant women experience unsuitable weight gain with WHO recommendations. This condition is associated with poor perinatal outcomes. Study investigates pregnancy weight gain's impact on outcomes. This study design was observational with a retrospective cohort approach. The sample size was obtained based on the difference formula of two proportions, namely, 142 mothers giving birth. Consecutive sampling technique according to inclusion criteria (mothers giving birth, willing to be respondents, complete medical record status) and exclusion extraction, namely having a history of comorbidities and/or complications The form record is used to collect data. Data analysis with SPSS 25 used the exact Fisher, Mann-Whitney, and chi-square tests. The results showed that 74% of pregnant women experienced weight gain not according to recommendations with 86.5% experienced inadequate weight gain. Appropriateness of weight gain during pregnancy was related to birth weight (p=0.024), birth length (p=0.009), amniotic fluid condition (p=0.000), and Apgar score (p=0.002). Pregnancy outcomes in the form of type of delivery (p=0.426), gestational age (p=0.84), and length of gestation (p=0.0583) were not related. Examination of pre-pregnancy BMI and education about recommendations for weight gain during pregnancy have been important since the first ANC contact.